Listening to the call of boredom at work: A Heideggerian journey into Michel Houellebecq's novels. (September 2022) - Culié, Jean-Denis; Meyer, Vincent; Philippe, Xavier
From the very first organizational theories, boredom at work has been closely linked to the issue of time. However, studies on boredom have often considered the phenomenon as a mere behavioral outcome of organizational processes or practices and have built on an instrumental approach, neglecting its deeper manifestations. Following recent calls to tackle boredom as a fundamental issue in organization studies, we build on Heidegger's framework to delve into superficial, retrospective, and profound boredom. This phenomenological approach enables us to go beyond the instrumental view of boredom, revealing the close links between boredom at work, time, and authenticity. To this end, we adopt a genuine empirical tool, immersed in the eight novels of the famous French writer, Michel Houellebecq, a unique observer of contemporary workers. Our findings help us to highlight two contributions. First, we argue that in trying to divert their employees from boredom by creating and developing "passing the time" activities, organizations only reinforce boredom at work, leading them to an unauthentic relationship with time and being. Second, we delve into the meanders of profound boredom at work and suggest that by listening to its call, individuals may unveil what truly matters to them and find a way to reach authenticity at work.